Pattern: Control the flow - Garcia, M.P.; Kern, Nergiz; Serrano, R.; Warburton, S. (Sense Publishers, 2014)
This pattern addresses the mechanics of synchronous text-based chat sessions for effective communication within online teaching sessions. © 2014 Sense Publishers. All Rights Reserved.
Keywords: [No Kerywords]